SPD_0410 negatively regulates capsule polysaccharide synthesis and virulence in Streptococcus pneumoniae D39 - Tao, Ye; Lei, Li; Wang, Shuhui; Zhang, Xuemei; Yin, Yibing; Zheng, Yuqiang (Frontiers in Microbiology, 2025)
Streptococcus pneumoniae capsular polysaccharide (CPS) is a crucial virulence factor for this pathogenic bacterium and is partially under transcriptional control. In this study, we used electrophoretic mobility shift assays and DNA enzyme footprinting to identified the hypothetical protein SPD_0410 as a negative regulator of cps locus. Our results showed that the D39Δspd0410 mutant strain exhibited significantly elevated CPS levels compared to the parental strain D39s. SPD_0410 directly binds at two specific sites on the cps promoter. The regulatory effect of SPD_0410 on CPS was weakened after the mutation of specific binding sites in the promoter. RNAseq analysis revealed that the deletion of spd0410 led to alterations in glucose metabolism. However, the altered glucose levels appeared to eliminate the regulation of CPS synthesis by SPD_0410. Deleting the spd0410 gene resulted in higher invasion and phagocytic resistance of bacteria and in vivo mouse experiments confirmed that D39Δspd0410 caused more severe systemic disease than the parental strain D39s. Our results indicated that SPD_0410 negatively regulates the synthesis of S. pneumoniae capsules and can directly alter pneumococcal virulence.